NEED ANALYSIS OF ETHNOPEDAGOGY-BASED THEMATIC LEARNING MODULES DEVELOPMENT FOR GRADE V ELEMENTARY SCHOOL STUDENTS IN PEKANBARU - Febrina Dafit; Zaka Hadikusuma Ramadan; Nuramalina Nuramalina; Alfian Yogi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The implementation of thematic learning in elementary schools is a new thing. One of the problems that occur in the implementation of thematic learning is the textbooks published by the Ministry of Education and Culture, which are compiled and used nationally, so it does not indicate the Ethno pedagogy of students' regions and students' knowledge about Indonesian culture, especially the culture in their regions that have still lack and educators do not have reference teaching materials that contain Ethno pedagogy-based thematic learning or instill local cultural values. Basically, thematic learning aims to introduce students to the environment that is closest to students. The purpose of the research is only to analyze and describe the need for the development of Ethno pedagogy-based thematic learning models for elementary school students in Pekanbaru so that the data used are qualitative data. The needs analysis of the development of Ethno pedagogy-based thematic learning modules includes curriculum analysis, student analysis, and teacher needs analysis. Various analyses were carried out to determine the need of developing a comprehensive Ethno pedagogy-based learning module based on the students’ conditions, curriculum, and teacher needs. A thorough and accurate needs analysis is expected to be developed for Ethnopedagogy-based thematic learning modules for grade V elementary school students in Pekanbaru that are based on the needs of the research field.